(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Implementation of Corporate Social Responsibility (CSR) of PT Toba Pulp Lestari Tbk in the Empowerment Program of the Berjuang Forest Farmers Group, Sipahutar District, North Tapanuli Regency. This research was conducted to examine the implementation and benefits of the CSR program by PT Toba Pulp Lestari Tbk in the form of empowerment of the Berjuang forest farmer group (KTH). The research was conducted using descriptive analysis methods with quantitative and qualitative approaches. This research was conducted with interviews and documentation as well as questionnaires where the variables were measured using the Likert scale rule to determine the criteria for interpreting the scores obtained. The results showed that the KTH Berjuang empowerment program by PT. Toba Pulp Lestari Tbk has played a good role in its implementation. This is evidenced by the first planting period which has been completed in several stages, namely providing land capital in the Plant Life Block, providing capital assistance, counseling and training in intercropping corn cultivation. Through this program a good relationship is established between the company and KTH Berjuang. The benefits of the profit dimension are the short-term plan for the first planting period of corn cultivation with the intercropping method, the results of which are fully the rights of KTH Berjuang, from the people dimension, which is helping to increase the knowledge and skills of farming members of KTH Berjuang, and from the planetary dimension, namely working together in preserving the area. Forests in order to achieve the sustainability of natural resources for the common good. The advice given is that the empowerment program must be applied consistently and continuously in order to achieve the program’s objectives, namely the independence of KTH Berjuang.